Atomically-thin non-layered cobalt oxide porous sheets for highly efficient oxygen-evolving electrocatalysts - Sun, Yongfu; Gao, Shan; Lei, Fengcai; Liu, Jiawei; Liang, Liang; Xie, Yi (Chemical science (Cambridge), 2014)
Water electrolysis for hydrogen production requires better catalysts to lower the kinetic barrier of the oxygen evolution reaction. Herein, conceptually-new, noble-metal-free, porous, atomically-thick sheets are first put forward as an excellent platform to promote the oxygen evolution activity through affording abundant catalytically active sites and enhanced two-dimensional conductivity. As an example, the synthetic porous Co sub(3)O sub(4) atomically-thick sheets with a thickness of 0.43 nm and about 30% pore occupancy afford low-coordinated Co super(3+) atoms to serve as the catalytically active sites, while the obviously increased density of states at the valence band and conduction band edge facilitate fast electron transport along their two-dimensional conducting paths. As a result, the porous, atomically-thick Co sub(3)O sub(4) sheets exhibit an electrocatalytic current up to 341.7 mA cm super(-2), roughly 50-times larger than that of the bulk counterpart and even more strikingly higher than that of most existing reports under similar conditions. This work holds great promise for triggering breakthroughs in the field of electrocatalysis.